Diatomáceas perifíticas indicadoras de contaminação orgânica no reservatório da Usina Hidrelétrica de Curuá-Una, Santarém, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Algae are known as the base of the trophic chain in aquatic systems, also considered great bioindicators of environmental conditions, responding immediately to changes in the environment, especially by the diatom group (Bacillariophyta). The present study aimed to carry out a survey of taxa of periphytic diatoms and relate their occurrence to variations in limnological conditions in two regions of the Reservoir of UHE de Curuá-Una, Santarém-PA. The samples were collected, during the years 2016 and 2017, using artificial substrates (EDS-type samplers). After collection, the samples were fixed for further oxidation, making permanent slides and counting 400 valves per sample, with the aid of an optical microscope. The abiotic variables were obtained with the aid of the multiparameter probe AKSO model AK88. For data analysis, the ANOVA One-way test was applied in order to observe the differences between the values of Shannon's Wealth and Diversity, as well as the PCA analysis (Principal Component Analysis) to verify the gradient of environmental variables, while CCA (Canonical Correspondence Analysis) to understand the significant relationships of environmental and spatial variables on the diatom community. The results showed that the analysis of the abiotic data indicated an accentuated spatial separation between the points, however no seasonal difference was observed. The result of the analysis of the abiotic variables showed that the highest turbidity values were recorded in the stations located in the central region of the hydroelectric lake (Point P2), as well as the highest BOD value. The periphytic diatom community was represented by 150 taxa, distributed in 19 genera. The most representative genera in number of taxa were Eunotia, Gomphonema, Brachysira and Fragilaria. Richness during sampling varied between 34 and 60 taxa. The lowest number of taxa was recorded in sample P1, located near the dam and the highest number was recorded in sample P2, located in the central region of the lake. Shannon's Diversity ranged between 2.43 and 3.26. The lowest Diversity value was observed in sample P1 and the highest value was observed in sample P2. The canonical correspondence analysis showed that there was a clear spatial separation of the samples. The present study showed that in the reservoir there is a strong tendency for the existence of a spatial variation of the species, coordinated by the abiotic variables, which in turn are influenced by the hydrological periods.
Keywords: Algas; Bioindicação; Diatomáceas; Perifíton; CNPQ:: CIÊNCIAS BIOLÓGICAS